Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1093/infdis/171.2.356
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Complications in the Treatment of Unsubstantiated Lyme Disease

Abstract: Treatment of unsubstantiated Lyme disease has led to serious complications in some cases. Two case-control studies, based on information in clinical records of patients discharged with a diagnosis of Lyme disease during 1990-1992, were conducted at a central New Jersey hospital. Twenty-five patients with biliary disease were identified, and 52 controls were selected from 1352 patients with suspected Lyme disease. Only 3% of 71 evaluatable subjects met the study criteria for disseminated Lyme disease. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 29 publications
2
49
0
2
Order By: Relevance
“…For the patients tested by the laboratories included in the above-mentioned study, the observed 4.6% decrease in specificity between the C6 EIA and standard 2-tiered testing would result in >100 000 additional falsepositive Lyme disease test results annually. Overdiagnosis of Lyme disease may result in unnecessary antibiotic administration as well as other adverse events [22][23][24]. For this reason, we still recommend that a supplemental immunoblot be performed for all children and adolescents with a positive C6 EIA result.…”
Section: Discussionmentioning
confidence: 99%
“…For the patients tested by the laboratories included in the above-mentioned study, the observed 4.6% decrease in specificity between the C6 EIA and standard 2-tiered testing would result in >100 000 additional falsepositive Lyme disease test results annually. Overdiagnosis of Lyme disease may result in unnecessary antibiotic administration as well as other adverse events [22][23][24]. For this reason, we still recommend that a supplemental immunoblot be performed for all children and adolescents with a positive C6 EIA result.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged antibiotic therapy may be harmful. In studies of patients with unsubstantiated Lyme disease, minor side effects were common (86), prolonged ceftriaxone therapy sometimes resulted in biliary complications (88), and in one reported case, the prolonged administration of cefotaxime resulted in death (89). Furthermore, prolonged use of antibiotics was recently associated with an increased risk of breast cancer (90).…”
Section: Figurementioning
confidence: 99%
“…Compared with penicillin, the advantages of ceftriaxone are its excellent cerebro-spinal fluid penetration and long serum half-life, which permits once-per-day dosing. However, ceftriaxone may cause biliary complications, which are not reported with cefotaxime administration [44].…”
Section: Arthritismentioning
confidence: 95%
“…Patients with arthritis plus objective evidence of neurological disease should receive parenteral therapy with ceftriaxone (at the single dose of 2 g daily; pediatric dose: 50-75 mg/kg per day with a maximum of 2 g daily) or, in alternative, cefotaxime or penicillin G at their standard dosage (see above) for 2-4 weeks [11,43,44]. According to some studies, in most cases 2 weeks of intravenous therapy with ceftriaxone is enough for resolving the illness [45,46].…”
Section: Arthritismentioning
confidence: 99%